2005
DOI: 10.1080/10473289.2005.10464749
|View full text |Cite
|
Sign up to set email alerts
|

Potential Interference Bias in Ozone Standard Compliance Monitoring

Abstract: The U.S. Environmental Protection Agency has established a federal reference method (FRM) for ozone (O 3 ) and allowed for designation of federal equivalent methods (FEMs). However, the ethylene-chemiluminescence FRM for O 3 has been replaced by the UV photometric FEM by most state and local monitoring agencies because of its relative ease of operation. Accumulating evidence indicates that the FEM is prone to bias under the hot, humid, and stagnant conditions conducive to high O 3 formation. This bias may lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 6 publications
1
39
2
Order By: Relevance
“…The costs of reducing O 3 pollution are estimated in the billions of dollars (Leston et al, 2005). For example, a report by the Instituto Nacional de Ecología (INE) in Mexico (McKinley et al, 2003) found that the implementation of several control measures could achieve a 3% reduction in daily maximum ozone concentration at the cost of approximately two billion dollars.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The costs of reducing O 3 pollution are estimated in the billions of dollars (Leston et al, 2005). For example, a report by the Instituto Nacional de Ecología (INE) in Mexico (McKinley et al, 2003) found that the implementation of several control measures could achieve a 3% reduction in daily maximum ozone concentration at the cost of approximately two billion dollars.…”
Section: Introductionmentioning
confidence: 99%
“…3164 E. J. Dunlea et al: Evaluation of UV ozone monitors counties in the U.S. have O 3 concentrations in excess of the threshold as a result of measurement interferences (Leston et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations